"I LOOKED OUT AND NATURE WAS GONE": language, lyric, and alterity in john kinsella's graphology poems 1995–2015. Issue 5 (3rd September 2018) - Disney, Dan
Abstract: In the nearly 800 pages that comprise the three volumes of his Graphology Poems 1995–2015 (Five Islands P, 2016), John Kinsella demonstrates an exemplary moral anger registering iterations of colonial "omni-speak" as unethical (1: 93). This paper reads Giorgio Agamben's Homo Sacer (Stanford UP, 1998) by way of apprehending the rhetorical substrata underpinning discourses of Australia as not just determining a sovereign colonial space; in a place where "history is absurdity […] history is overlay" ( Graphology Poems 1: 158), Kinsella shows how indigenous and non-colonial others are consistently cast as extra-juridical and merely sub-human. These Graphology Poems not only anathemise and hex historical falsehoods of nation: Kinsella dares sound out the bullshit, and his iconoclastic language games refuse outright to acquiesce to the epistemically violent nullifications of antipodean identity.